Susceptibility to Thrombin-Induced Platelet Microbicidal Protein Is Associated with Increased Fluconazole Efficacy against Experimental Endocarditis Due to Candida albicans - Yeaman, Michael R. (American Society for Microbiology, 2004)
Platelet microbicidal proteins (PMPs) are believed to be integral to host defense against endovascular infection. We previously demonstrated that susceptibility to thrombin-induced PMP 1 (tPMP-1) in vitro negatively influences Candida albicans virulence in the rabbit model of infective endocarditis (IE). This study evaluated the relationship between in vitro tPMP-1 susceptibility (tPMP-1(s)) or resistance (tPMP-1(r)) and efficacy of fluconazole (FLU) therapy of IE due to C. albicans. Candida IE was established in rabbits with either tPMP-1(s) or tPMP-1(r) strains. Treatment groups received FLU (100 mg/kg/day) intraperitoneally for 7 or 14 days; control animals received no therapy. At these time points, cardiac vegetations, kidneys, and spleens were quantitatively cultured to assess fungal burden. At both 7 and 14 days and in all target tissues, the extent of candidal clearance by FLU was greater in animals infected with the tPMP-1(s) strain than in those infected with the tPMP-1(r) strain. These differences were statistically significant in the spleen and kidney. Corroborating these in vivo data, FLU (a candidastatic agent), in combination with tPMP-1, exerted an enhanced fungicidal effect in vitro against tPMP-1(s) and tPMP-1(r) C. albicans, with the extent of this effect greatest against the tPMP-1(s) strain. Collectively, these results support the concept that tPMP-1 susceptibility contributes to the net efficacy of FLU against C. albicans IE in vivo, particularly in tissues in which platelets and tPMP-1 likely play significant roles in host defense.